Comparative evaluation of the mass loss of two composite resins after tooth brushing with abrasive cream (Research, Society and Development, 2024)
Researchers have improved the quality of composite resins due to the great emphasis being given to aesthetics in the restorative area in relation to the use of restorations in anterior teeth, restoring their natural appearance that meets the demands imposed by patients. Although composite resins still have deficiencies, the search for a material that restores the lost portion of the tooth, bringing it closer to its natural form, is the purpose of research. The objective of this study was to compare in vitro the change in mass loss between nanoparticle composite resin and microparticle composite resin, both subjected to the action of simulated brushing with abrasive toothpaste. They prepared 32 test specimens, 16 of each material, followed the manufacturer's instructions, and then standardized finishing and polishing on all test specimens with continuous hydration. They proceeded to weigh the test specimens three times on a four-digit digital scale with values ​​in grams, obtaining the arithmetic mean of the test specimens of each sample and recording it in a table containing the weights that determined the initial mass of the material examined. Abrasion tests were performed on a brushing machine with toothpaste and water solution, recording 100,000 cycles and a load of 200 g. After the brushing process, the test specimens were weighed again and these values ​​recorded as the final mass. They concluded that after simulated brushing, there was a loss of mass between the two resins; however, the microhybrid resin showed greater wear than the nanoparticle resin.